An approach to the study of the conversation between patients with alzheimer and their healthy interlocutors - Valles, Beatriz (Revista de Investigación en Logopedia, 2013)
This research aimed to study the conversation of people with dementia and their healthy interlocutors in the home context. The following objectives were proposed: 1) To analyze the variety of conversational resources (turns to speak, adjacent pairs, use of repairs and/or marks) used by all interlocutors (patients, caregivers and researcher); 2) To study how the use of these resources may or may not have an influence in the structure of the conversation; and 3) To value the use of other forms of non-linguistic communication, such as the use of gestures, for instance. The informants were two dementia patients, their caregivers and the researcher. In order to make the corpus, four linguistic interactions with all the participants were filmed in video during the period of one year. Some segments of the conversations were selected, transcribed into gloss and later analyzed. The results show that the dementia patients used discursive marks, the typical response of adjacent pairs, repetitions and paraphrases. When comparing both performances, we observed a marked difference in the length of their turns to speak and in the use of complex sentence structures. One of the patients used gestures as substitute for words. Both caregivers used repetition and addition of information, and adjusted their linguistic performance to the situation. The researcher used linguistic markers and questions to introduce the conversation, which had an influence on the organization of the speech, in a question-answer format, as in therapeutic or supervised interviews. The turns to speak developed in an coordinated way. The contributions of this study are considered important to deepen our current knowledge on the conversation of patients with dementia and the role played by their regular interlocutor in this process.